Dynamics of Islamic Education Institution Development Program in Facing the Era of Globalization Studies - Neliwati, Neliwati; Saripuddin B, Muhammad; Novriadi Cibro, Andika; Kaloko, Burhanuddin; Syafnial, Syafnial (STAI Miftahul Ula Nganjuk, 2023)
The purpose of this study is to discuss the dynamics of the Islamic education institution development program in the face of the globalization era at the Darul Muta`allimin Tanah Merah Aceh Singkil Islamic Boarding School, the research method used is qualitative, the results of this study are: a). Classification of the education system at the Darul Muta`allimin Tanah Merah Aceh Singkil Islamic Boarding School has various educational units classified by researchers into four types of systems, namely (1) the Islamic boarding school education system (recitations using classical books), (2) the Islamic boarding school education system public school education (Darmut Middle School and Darmut MA), (3) madrasah education system (Diniah Darmut Madrasah), (4) life skills or organizational education system (Scout, PMR, Calligraphy, Hadrah etc). b). Islamic boarding schools have educational units that include the national curriculum, as well as mental stabilization of the students to face this era of increasingly rapid globalization by holding organizational activities such as scouts and PMR to add to the social sense of the students. c). Pondok Pesantren Darul Muta`allimin Tanah Merah Aceh Singkil has two forms of dynamics in its education system, namely physical and non-physical, for physical forms such as building construction and equipping facilities for education and for non-physical forms, namely institutional renewal and curriculum renewal (from only using the form of a book recitation system in general to using the government curriculum or there are class gaps in formal and non-formal schools). as well as the mental stabilization of the students to face this increasingly rapid era of globalization by holding organizational activities such as scouts and PMR to add to the social sense of the students. c). Pondok Pesantren Darul Muta`allimin Tanah Merah Aceh Singkil has two forms of dynamics in its education system, namely physical and non-physical, for physical forms such as building construction and equipping facilities for education and for non-physical forms, namely institutional renewal and curriculum renewal (from only using the form of a book recitation system in general to using the government curriculum or there are class gaps in formal and non-formal schools). as well as the mental stabilization of the students to face this increasingly rapid era of globalization by holding organizational activities such as scouts and PMR to add to the social sense of the students. c). Pondok Pesantren Darul Muta`allimin Tanah Merah Aceh Singkil has two forms of dynamics in its education system, namely physical and non-physical, for physical forms such as building construction and equipping facilities for education and for non-physical forms, namely institutional renewal and curriculum renewal (from only using the form of a book recitation system in general to using the government curriculum or there are class gaps in formal and non-formal schools).